Biorefining of platinum group metals from model waste solutions into catalytically active bimetallic nanoparticles. Issue 2 (28th December 2017) - Murray, Angela J.; Zhu, Ju; Wood, Joe; Macaskie, Lynne E.
Summary: Bacteria can fabricate platinum group metal (PGM) catalysts cheaply, a key consideration of industrial processes and waste decontaminations. Biorecovery of PGMs from wastes is promising but PGM leachates made from metallic scraps are acidic. A two‐step biosynthesis 'pre‐seeds' metallic deposits onto bacterial cells benignly; chemical reduction of subsequent metal from acidic solution via the seeds makes bioscaffolded nanoparticles (NPs). Cells of Escherichia coli were seeded using Pd(II) or Pt(IV) and exposed to a mixed Pd(II)/Pt(IV) model solution under H2 to make bimetallic catalyst. Its catalytic activity was assessed in the reduction of Cr(VI), with 2 wt% or 5 wt% preloading of Pd giving the best catalytic activity, while 1 wt% seeds gave a poorer catalyst. Use of Pt seeds gave less effective catalyst in the final bimetallic catalyst, attributed to fewer and larger initial seeds as shown by electron microscopy, which also showed a different pattern of Pd and Pt deposition. Bimetallic catalyst (using cells preloaded with 2 wt% Pd) was used in the hydrogenation of soybean oil which was enhanced by ~fourfold using the bimetallic catalyst made from a model waste solution as compared to 2 wt% Pd preloaded cells alone, with a similar selectivity to cis C18:1 product as found using a Pd‐Al2 O3 commercial catalyst. Abstract : Bacterial cells pre‐seeded with Pd(0) make catalytically active metallic nanoparticles when supplemented with mixed Pd/Pt solution. Pt is less able to supply this seeding function and the subsequent catalyst is less active catalytically. This is attributed to fewer, larger nanoparticles than with cells pre‐seeded using Pd.